Displaced Identities and Traveling Texts in Luisa Valenzuela's Black Novel (With Argentines) - Laura R. Loustau (Studies in 20th & 21st Century Literature, 2008)
In Luisa Valenzuela's Black Novel (With Argentines) Roberta and Agustín, the main characters, cross geographic, physical, psychological, sexual and textual borders in order to regain their own writing space, one which would allow them to narrate their own past. Themes that include exile, memory, and literary and artistic creations are presented from a theatrical and deterritorialized space. In Black Novel the city of New York is the stage where the characters/actors create and mix together space and time coordinates. The intention is to (re)construct the individual memory of the characters, and in a more ample perspective, the collective memory of a society that lived under institutionalized repression. In the processes of (re)constructing memory, the limits of human behavior and the mechanisms of knowledge are questioned.
Keywords: Luisa Valenzuela; Black Novel (With Argentines); exile; memory; literary creation; artistic creation; New York; recreation of space; collective memory; repression; knowledge